The trophy hunting of African lions: scale, current management practices and factors undermining sustainability. - Peter Andrew Lindsey (Public Library of Science (PLoS), 2013)
The trophy hunting of lions Panthera leo is contentious due to uncertainty concerning conservation impacts and because of highly polarised opinions about the practice. African lions are hunted across at least ~558,000 km(2), which comprises 27-32% of the lion range in countries where trophy hunting of the species is permitted. Consequently, trophy hunting has potential to impart significant positive or negative impacts on lions. Several studies have demonstrated that excessive trophy harvests have driven lion population declines. There have been several attempts by protectionist non-governmental organisations to reduce or preclude trophy hunting via restrictions on the import and export of lion trophies. We document the management of lion hunting in Africa and highlight challenges which need addressing to achieve sustainability. Problems include: unscientific bases for quota setting; excessive quotas and off-takes in some countries; fixed quotas which encourage over-harvest; and lack of restrictions on the age of lions that can be hunted. Key interventions needed to make lion hunting more sustainable, include implementation of: enforced age restrictions; improved trophy monitoring; adaptive management of quotas and a minimum length of lion hunts of at least 21 days. Some range states have made important steps towards implementing such improved management and off-takes have fallen steeply in recent years. For example age restrictions have been introduced in Tanzania and in Niassa in Mozambique, and are being considered for Benin and Zimbabwe, several states have reduced quotas, and Zimbabwe is implementing trophy monitoring. However, further reforms are needed to ensure sustainability and reduce conservation problems associated with the practice while allowing retention of associated financial incentives for conservation.